Cấu trúc các lớp điện ly tại khu vực phía nam trogn giai đoạn mặt trời hoạt động mạnh (200-2002) - Lan, Hoàng Thái (Vietnam Journal of Earth Sciences, 2003)
Structure of the ionospheric layers observed at south Vietnam during the period of high solar activity (2000-2002)